Study and Critical Edition of the Treatise "Tafsīr (mā kāna ʻalá al-Nabīyy) by Muḥammad ibn Muḥammad Altıparmak - Champil Serif Damadoglou (Al-Qanṭara, 2025)
This article deals with the study of the scholarly biography of Muḥammad ibn Muḥammad, known as Altıparmak (d:1033 AH). He was one of the most prominent scholars and Sufi personalities in the 17th century. In this article, the writer aims to examine the exegetical interpretation Altıparmak, conveyed in the exegesis of the thirty-eighth verse of Surat Al-Ahzab, based on the author's original manuscript. This article is significant as it is the first of its kind that deals with this investigation. In this brief exegesis, Altıparmak discussed the issue of the marriage of the Prophet (pbuh), to the mother of believers, Zaynab bint jaḥsh. He explained behind this marriage thus: " there would be no blame on the believers for marrying the ex-wives of their adopted sons after their divorce." It is worth mentioning that this is one of the possible interpretations that crossed the mind of Altıparmak and one of the esoteric meanings he grasped after reading this verse. He read the esoteric interpretation of this noble verse, and the reading by Altıparmak is considered an exploratory and indicative reading aimed at revealing the secrets of meanings and lifting the curtain on the jewels and components of this venerable verse.